Atomistic simulation studies of nickel and cobalt doped manganese-based cathode materials - Tsebesebe, Nkgaphe Tebatjo (My University, 2021)
The stead-fast demand for sustainable lithium-ion batteries (LIB) with competitive electrochemical properties, safety, reduced costs, and long-life cycle, calls for intensive efforts towards the development of new battery cathode materials. The layered transition metal oxides formulated LiMO2 (M: Mn, Ni and Co) have attracted considerable attention due to their capability to optimize the discharge capacity, cycling rate, electrochemical stability and lifetime. The transition metals Mn, Ni and Co (NMC) have been reported to contribute towards enhancement of the performance of NMC based lithium-ion batteries. In this work, the electronic properties of transition metal oxides LiMO2 (M: Mn, Ni and Co) as individual crystal structures are studied using density functional theory (DFT+U) in the local density and generalized gradient approximation (LDA and GGA). The Hubbard U values together with the low spin transition metal in 3+ charge state (Mn3+, Ni3+ and Co3+) predicts the electrical conductivity of the materials. The conductivity is associated predominantly with 3d states of the transition metals (Mn, Ni and Co) and 2d character in oxygen. The LiNiO2 material is high in conductivity, while both LiMnO2 and LiCoO2 are low in electrical conductivity. All independent elastic constants satisfy the mechanical stability criterion of orthorhombic materials implying stability of the materials. However, the phonon dispersion curves display imaginary vibration along high symmetry direction for LiCoO2. The heats of formations predict that the LiNiO2 is the most thermodynamically stable material while the LiMnO2 is the least thermodynamically stable material. The derived interatomic potentials produced NiO and CoO structures with a difference of less than 1% and 9% respectively, from the experimental structures. The structures were melted at temperatures close to their experimental values from molecular dynamics. The radial distribution curves and Nano architectures presented the melting point of NiO and CoO at 2250K and 2000K respectively. All independent elastic constants satisfy the mechanical stability criterion of cubic materials implying stability of the materials. The high electrical conductivity and thermodynamic favourability LiNiO2 suggests that the material can be the most recommendable material as a cathode material and further improved through doping. This will add the overall enhancement of the electrochemical performance while stabilizing structural stability of the cathode material in high energy density Li-ion batteries.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2021
Keywords: Manganese alloys; Doped semiconductors; Lithium ion batteries; Transition metal oxides; Cobalt-nickel alloys; Manganese alloys; Doped semiconductors; Lithium ion batteries; Transition metal oxides; Cobalt-nickel alloys